O dever de transparência da administração pública e a divulgação de informações pessoais dos agentes públicos: um conflito entre o interesse público e os direitos fundamentais à intimidade e à vida privada - Ritter, Renée Cristina Herlin (Universidade do Vale do Rio dos Sinos, 2015)
The changes occurred in the field of Democratic States of Law, while positive, also contributed to the government's crisis by failing to meet the new expectations, leading to the weakening of the credibility of the citizens and demotivating them to integrate the system whose representation lost status of a capable instrument that faces so many challenges. Therefore, the most provocative proposal to current democracies is to allow, via a communication network between the Public Administration and the administered, the strengthening of popular participation as to obtain the efficiency of public activity, as a way to rule that fits in with the people, the ones who are the most interested. In this context, administrative transparency emerges as a suitable means to strengthen such relationship, especially by making use of the available technological tools, thus establishing public accessibility as a rule and secrecy as the exception. It is through the theoretical and analytical method, therefore, that we aim to verify whether the disclosure of information in websites effectively contribute to the fulfillment of the obligation of transparency, as well as the citizens' rights to obtain information on the Public Administration, resulting - in return - in limitations to fundamental rights to the privacy of public officials, who have personal data provided because of constitutional duties. What - sheltering on the justification rendered in the Supreme Court to do so - leads to discussion about the validity of restricting fundamental rights at the expense of what is called public interest.
Keywords: Estado democrático de direito; Publicidade administrativa; Direitos fundamentais; Interesse público; Democratic rule of law; Public accessibility; Fundamental rights; Public interest; ACCNPQ::Ciências Sociais Aplicadas::Direito